Evaluation of Wound Healing Activity of Herbal Formulation - JAIN, AVIJEET; PALIWAL, VIVEK; JAIN, ANUREKHA; DEB, LOKESH; GUPTA, ARUN (Asian Journal of Chemistry, 2010)
The wound healing activity of one herbal formulation (Zakhme heal ointment) containing Rai, Suhaga, Fitkari, Swarnageru, Singdaraj in paraffin base was evaluated for its wound healing potential in two types of wound models in rats (i) excision wound model and (ii) incision wound model. The formulations responded significantly in both the wound models tested. The results were also comparable to that of the standard drug nitrofurazone used as a standard drug for comparison in this present investigation. The results were also comparable in terms of wound contracting ability, epithelialization period, tensile strength and regeneration of tissues at the wound area. Thus, this investigation confirms the use of the Zakhme heal ointment as wound-healing formulation.